Reductions in Blood Lead Level Screening During Peak COVID‐19 Restrictions and Beyond - Meghan L. McCarthy; Jonah Bradenday; Elizabeth Chen; Mark R. Zonfrillo; Indra Neil Sarkar (Public Health Challenges)
ABSTRACT Background and Objectives Among the multitude of health effects on children associated with the COVID‐19 pandemic, there have been significant interruptions in the provision of routine pediatric primary care, including blood lead level (BLL) screening. We aimed to investigate trends in BLL screening before and during the pandemic era using patient‐level electronic health record data extracted from CurrentCare, Rhode Island's statewide health information exchange (HIE). Methods De‐identified data were analyzed from CurrentCare for the study period January 2018 to December 2021. We utilized ATLAS, a web‐based analytics platform from the Observational Health Data Sciences and Informatics (OHDSI) community, to extract and stratify BLL by variables of interest from the CurrentCare data, standardized to OHDSI's Observational Medical Outcomes Partnership common data model. Results A decrease in BLL screening occurred in the spring of 2020, aligning with initial periods of shelter‐in‐place in response to the novel coronavirus outbreak; there was a 48% decrease comparing quarter 2 (April to June) of 2019 and 2020. BLL screening rebounded in the summer of 2020, however, it remained 16% lower overall in 2020 than in 2019. In 2021, BLL screening fell again to 23% lower than in 2019. Although overall numbers of BLL screenings were reduced, the proportion of abnormal BLLs was higher, particularly in the range of 3.5–5.0 µg/dL. Conclusions Leveraging statewide HIE data, we found that significant deficiencies in BLL screening remain unresolved since the beginning of the COVID‐19 pandemic. The disruption of children's lives by the COVID‐19 pandemic appears to have greatly affected lead screening and exposure in Rhode Island.